1998
DOI: 10.1177/1087724x9800200309
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Brownfield Redevelopment: Lessons Learned from Two Great Lakes States

Abstract: This article examines the barriers to brownfield redevelopment through a case study analysis of four cities in two Great Lakes states. Four key barriers are identified and investigated: legal liability, limited information, limited financial resources, and limited demand for the properties. Perceived liability emerges as a dominant barrier, and one that compounds the other three barriers. The article analyzes how and why liability perceptions affect stakeholder behavior and provides lessons learned for promoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 4 publications
0
17
0
Order By: Relevance
“…Most studies that have examined the redevelopment of contaminated properties have identified the barriers to redevelopment and how direct financial subsidies and other interventions can improve the attractiveness of investing in such properties (Bartsch, Undated;Bartsch, Collaton, & Pepper, 1996;Coffin & Shepherd, 1998;DeSousa, 2004;Howland, 2003Howland, , 2004Pepper, 1997;Wernstedt, 2001;XL International and International Economic Development Council, 2002;Yount & Meyer, 1999). Sherman (2003) provides the most thorough work on financial subsidies in his simulations of developer investment calculations, including property tax abatements, site assessment grants, development grants, low-interest loans for assessment and remediation, and federal tax incentives that allow remediation costs to be written off for tax purposes as expenses in the year they are incurred (rather than depreciated over a project life).…”
Section: Existing Literaturementioning
confidence: 97%
“…Most studies that have examined the redevelopment of contaminated properties have identified the barriers to redevelopment and how direct financial subsidies and other interventions can improve the attractiveness of investing in such properties (Bartsch, Undated;Bartsch, Collaton, & Pepper, 1996;Coffin & Shepherd, 1998;DeSousa, 2004;Howland, 2003Howland, , 2004Pepper, 1997;Wernstedt, 2001;XL International and International Economic Development Council, 2002;Yount & Meyer, 1999). Sherman (2003) provides the most thorough work on financial subsidies in his simulations of developer investment calculations, including property tax abatements, site assessment grants, development grants, low-interest loans for assessment and remediation, and federal tax incentives that allow remediation costs to be written off for tax purposes as expenses in the year they are incurred (rather than depreciated over a project life).…”
Section: Existing Literaturementioning
confidence: 97%
“…There have been many case studies describing some of the characteristics of the contaminated properties, which include the history of the property, location, the contamination, liability concerns, costs of remediation, and the incentives used to promote the remediation and redevelopment of the property (Page and Rabinowitz, 1994;Pepper, 1997;Bartsch et al, 1997;Coffin and Shepherd, 1998;Collins and Savage, 1998;De Sousa, 2000).…”
Section: Literature Reviewmentioning
confidence: 98%
“…The increasing number of projects and research platforms demonstrates the increasing interest of policy makers, too (see the summary reports on activities, products and tools developed by previous brownfield projects by Tölle (2009) or Frantál et al, (2012). Many previous studies have investigated and conceptualized drivers and barriers of brownfields redevelopment -whether on the basis of stakeholder surveys or interviews with experts (Adair et al, 2002;Alberini et al, 2005;De Sousa, 2000;Letang and Taylor, 2012) or assessments of a limited number of local case studies (Coffin and Shepherd, 1998;Dixon, 2007;Dixon et al, 2011;Nijkamp et al, 2002).…”
Section: Introductionmentioning
confidence: 98%